2022
DOI: 10.1093/ofid/ofac488
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Multistep Bundles Intervention in the Management and Outcome of Gram-Negative Bloodstream Infections: A Single-Center “Proof-of-Concept” Study

Abstract: Background This is a “proof-of-concept” study aiming to evaluate the impact of a multi-step bundles intervention in the management and outcome of patients with Gram-negative bloodstream infections (GN-BSIs). Methods This was a single-center, quasi-experimental design study. In the pre-phase (January 2019 to May 2020), patients were retrospectively enrolled. During the post-phase (June 2020 to September 2021), all patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…The results of these antibiotic stewardship strategies in terms of mortality risk reduction in our population are in line with the current literature [ 28 ]: inappropriate use of antibiotics can cause antibiotic resistance up to emergency levels, multiple adverse events, further secondary infections, and in turn, deaths. Accordingly, this work supports the importance of providing stewardship interventions, also in the context of the COVID-19 pandemic [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 84%
“…The results of these antibiotic stewardship strategies in terms of mortality risk reduction in our population are in line with the current literature [ 28 ]: inappropriate use of antibiotics can cause antibiotic resistance up to emergency levels, multiple adverse events, further secondary infections, and in turn, deaths. Accordingly, this work supports the importance of providing stewardship interventions, also in the context of the COVID-19 pandemic [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 84%
“…Additional risk factors for mortality emerging from this study were older age, septic shock, and delayed appropriate antimicrobial therapy, as frequently reported by other studies conducted on gram-negative bacterial BSI [ 2 , 9 11 , 19 , 20 ]. Importantly, to improve the outcome of BSIs, many additional factors are determinant: for instance, a multi-step bundle approach to manage gram-negative bacterial BSI may be beneficial, improving the identification of deep sites of infections and rate of early targeted antimicrobial therapy and allowing rapid discontinuation of antibiotics in cases of uncomplicated BSIs, preventing adverse events [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…CRAB-BSI occurred with septic shock, acute lung failure, and acute kidney failure in 36%, 42%, and 31% of patients, respectively. At presentation, the median SOFA score was 5 (2-6), and 30 (25%) patients had a PITT bacteriemia score [ 4. All CRAB isolates were sensitive to colistin [median (q1-q3) MIC = 0.5 (0.5-1) mg/l] and to cefiderocol [median (q1-q3) disk diffusion diameter 20 (18)(19)(20)(21)(22) mm], except two strains which were resistant to cefiderocol at baseline. Of note, all the strains were resistant to aminoglycosides, carbapenems, fluoroquinolones, and ampicillin/sulbactam; finally, tigecycline sensitivity (MIC B 2 mg/l) was documented in 11 (9%) cases.…”
Section: General Characteristics Of the Study Population And Crab-bsimentioning
confidence: 99%
“…Indeed, in a recent study, the benefit of a multi-step bundles approach aimed at managing BSIs by Gram-negative bacteria as a "clinical syndrome" was demonstrated; mortality was reduced by improving the identification of deep sites of infections, the rate of early targeted antimicrobial therapy, and the rapid discontinuation of antibiotics in cases of uncomplicated BSIs [71]. These bundles should also be used in cases of SM infections; in fact, as occurred in the study conducted by Sarzynski and co-workers [44], patients in the levofloxacin group showed a reduced mortality probably because they were more likely to receive an early effective empirical therapy (10% versus 0.9%).…”
Section: Limitationsmentioning
confidence: 99%